Migrant Scholars Researching Migration Reflexivity, Subjectivity and Biography in Research - Gemignani, Marco; Hernández-Albújar, Yolanda; Sládková, Jana (Taylor & Francis, 2024)
Language Order, antropology, biographical research, biography, careers, experiences, geography, methodology, migrants, migration, objectivity